Peran Guru Dalam Pelaksanaan Gerakan Literasi Sekolah Dan Dampaknya Terhadap Minat Baca Siswa SD Panongan II Tangerang - Adelia Mairina Lestari; Zahra Isnasywa (Indo Publishing, 2026)
The problems in implementing the School Literacy Movement are still closely related to the role of teachers in fostering students' interest in reading through literacy activities in elementary schools. Teachers have not been fully able to optimize reading activities consistently, so that they have not had an impact on students' reading culture evenly. This study aims to analyze the role of teachers in implementing the School Literacy Movement and its impact on students' interest in reading at SD Panongan II Tangerang. This study uses a qualitative approach with a case study method. The research subjects consisted of two classroom teachers and two third and fifth grade students. Data collection techniques included observation, interviews, and documentation. The results of this study indicate that teachers play the role of facilitators, motivators, and mentors in literacy activities through scheduled reading, 15 minutes of reading before class, and follow-up activities such as writing and presenting the results of their reading. However, the role of teachers has not been optimal due to limited literacy facilities, variations in reading materials, student characteristics, and the influence of gadget use, which affects students' interest in reading. Permasalahan dalam pelaksanaan Gerakan Literasi Sekolah masih berkaitan erat dengan peran guru dalam menumbuhkan minat baca siswa melalui kegiatan literasi di sekolah dasar. Guru belum sepenuhnya mampu mengoptimalkan kegiatan membaca secara konsisten sehingga belum berdampak pada budaya membaca siswa secara merata, penelitian ini bertujuan untuk menganalisis peran guru dalam pelaksanaan Gerakan Literasi Sekolah serta dampaknya terhadap minat baca siswa di SD Panongan II Tangerang. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Subjek penelitian terdiri atas dua guru kelas dan dua siswa kelas III dan V. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa guru berperan sebagai fasilitator, motivator dan pembimbing dalam kegiatan literasi melalui pelaksanaan membaca terjadwal, membaca 15 menit sebelum pembelajaran serta kegiatan lanjutan berupa menulis dan mempresentasikan hasil bacaan. Namun, peran guru belum berjalan optimal akibat keterbatasan sarana literasi, variasi bahan bacaan, karakteristik siswa serta pengaruh penggunaan gadget yang memengaruhi minat baca siswa